Planning and Development of Land Act, 1997, Draft - Government of the Republic Trinidad and Tobago. (Government of the Republic Trinidad and Tobago., 2011)
An Act for the orderly and progressive development of land and to preserve and improve the amenities thereof, for granting permission to develop land and other powers of control over the use of land, the design, construction and occupation of buildings.
Keywords: National Physical Planning Commission (NPPC), Development planning Laws - Trinidad and Tobago, Land development – Legislation, Environmental management, Regional planning, Environmental protection, Sustainable development, Construction - Laws